Psychiatry and Psychotherapy. The principle of complementarity - M. S. Chistyakov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article considers conceptual frameworks underlying the psychiatric and psychotherapeutic approaches to the mental disorders. The attention is drawn to the considerable differences between these approaches, as regards the doctor’s therapeutic position, focus of attention in the diagnostic process, means of treatment, definitions and descriptions of normality, accepted in these approaches. It is offered, for convenience of the clinical practice, to consider these approaches as the relatively independent, but at the same time as the complementary ones, in accordance with the principle of complementarity, formulated by physicist N. Bohr in quantum mechanics for systematization of the data, received in different circumstances of observation, by the observers with different attitudes. The author offers to consider every patient with mental disorder in clinical practice from the points of view of these 2 axes (the psychiatric medical approach and the psychotherapeutic approach) independently.